2014
DOI: 10.1007/s13142-014-0263-2
|View full text |Cite
|
Sign up to set email alerts
|

Using response variation to develop more effective, personalized behavioral medicine?: evidence from the Resist Diabetes study

Abstract: Health behavior interventions have achieved some notable outcomes through generally higher dose interventions with intensive initial phases and longterm, faded contact maintenance phases with attention to mean changes and adherence rates. Interventions may be improved by shifting attention to the very large response variation that is typical for such protocols as exercise with non-, low, moderate, and high responders and even those who show adverse responses. Data from the Resist Diabetes study, which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
(33 reference statements)
2
6
0
Order By: Relevance
“…For example, for glucose control variables, several authors have observed that after 3 months of strength training (2 days/week, 2 strength exercises at maximal effort), the NRs prevalence for improvements in an OGTT in pre-diabetic patients was 44%. In the present study, we found a NRs prevalence of 15 and 25% in the H-IR and L-IR groups, respectively, for decreased fasting glucose, with no significant difference between the groups (to see Table 3 ; Winett et al, 2014 ). Regarding HOMA-IR, the HERITAGE study (Boulé et al, 2005 ) showed that after 20 weeks of endurance training [30–50 min/session, 55–75% maximum oxygen uptake (VO 2 max) for 20 weeks], 42% of subjects were NRs for a decrease in HOMA-IR scores.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…For example, for glucose control variables, several authors have observed that after 3 months of strength training (2 days/week, 2 strength exercises at maximal effort), the NRs prevalence for improvements in an OGTT in pre-diabetic patients was 44%. In the present study, we found a NRs prevalence of 15 and 25% in the H-IR and L-IR groups, respectively, for decreased fasting glucose, with no significant difference between the groups (to see Table 3 ; Winett et al, 2014 ). Regarding HOMA-IR, the HERITAGE study (Boulé et al, 2005 ) showed that after 20 weeks of endurance training [30–50 min/session, 55–75% maximum oxygen uptake (VO 2 max) for 20 weeks], 42% of subjects were NRs for a decrease in HOMA-IR scores.…”
Section: Discussionsupporting
confidence: 49%
“…There is limited evidence about interindividual variability in exercise training with regard to the NRs prevalence in subjects with low glucose control, and there are several methodological differences in studies comparing the NRs prevalences observed in previous studies (Boulé et al, 2005 ; Gremeaux et al, 2012 ; Yates et al, 2013 ; Moker et al, 2014 ; Winett et al, 2014 ; Higgins et al, 2015 ). For example, for glucose control variables, several authors have observed that after 3 months of strength training (2 days/week, 2 strength exercises at maximal effort), the NRs prevalence for improvements in an OGTT in pre-diabetic patients was 44%.…”
Section: Discussionmentioning
confidence: 99%
“…The overall retention rate was 76% ( Fig 1 ). Adherence to the twice weekly RT sessions during the 3-month Initiation Phase was 91% (i.e., 22 of 24 sessions completed) [ 34 ]. Self-reported adherence among those present at assessment sessions, using the time-line follow-back calendars completed at month 9, was 78% and 72% in the SCT and Standard groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…While there is unequivocal evidence for PA improving population and participant group mean values, indicating positive changes in the majority of participants within the data, it is evident that there is considerable variation in the magnitude of response to exercise interventions within the population: with some individuals displaying considerably greater changes in a variety of health-related outcome measures than others, despite adhering to the same exercise regimen. 98 Additionally, the magnitude of change in one factor, such as VO 2 peak , is not necessarily associated with the magnitude of change in another factor. For example, in the HART-D study, a 9-month exercise training intervention for patients with T2DM, 99 57% of participants displayed an increase in their peak oxygen uptake (VO 2 peak ), while the remaining 43% exhibited no change.…”
Section: Methodsmentioning
confidence: 99%